The role of structured exercise interventions on cognitive function in older individuals with stable Chronic Obstructive Pulmonary Disease: A scoping review - Eastus, Caroline C.; Baez, Daniel E.; Buckley, Maria L.; Lee, Jungeun; Adami, Alessandra (Frontiers in Rehabilitation Sciences, 2022)
A decline in cognitive performance has been associated with disease severity, exacerbations rate, presence of comorbidities, and low activity level in people with chronic obstructive pulmonary disease (COPD). Participation in exercise programs appears to have neuroprotective effects and to improve cognitive performance in older people. The present work undertook a scoping review of the effects of exercise-based interventions on cognitive function in older individuals with stable COPD. Methods The methodological framework for scoping review was used and electronic searches of five databases performed. Original research and observational studies published between January 2010 and December 2021, administering exercise-based interventions and cognitive function evaluation, were included. Results Of 13 full-text manuscripts assessed for eligibility, five were allocated to analysis. Three studies administered exercise training within pulmonary outpatient rehabilitation program (PR), and one inpatient PR. The fifth study conducted a structured training intervention in which either aerobic or a combination with resistance exercises were included. Twelve cognitive function screening tools were used in the five studies included in the analysis. Results extracted were based on 245 COPD (33% female) with moderate to very-severe airflow limitation. Interventions ranged from 12 to 36 sessions. Studies reported statistically significant improvements after intervention in different cognitive function domains, such as global cognition, immediate and delayed recall ability, cognitive flexibility, verbal fluency, attention, abstract reasoning, praxis ability. Conclusions Exercise-based interventions improve several areas of cognitive function in patients with stable COPD. However, the magnitude of gain varies among studies, and this is possibly due to the heterogeneity of tests used. Future research is needed to validate the optimal battery of screening tests, and to support the definition of guidelines for cognitive function evaluation in COPD.